Sistem Informasi Managemen Data Kaveling Pada PT. Surabaya Industrial Estate Rungkut - Ilham Eka Fauzi; Arifin Puji Widodo; Teguh Sutanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Surabaya Industrial Estate Rungkut – SIER (Persero) are state-owned enterprise who work on planning, developing and managing industry district of SIER, PIER and Berbek. Any data about kavling are critical and important that is used as main transaction for marketing, which means up to date data are necessary. However, there is a management process problem for matching data takes up to 48 hours and this resulted as delayed transactions, starting from 12 hours up to 48 hours of delays transactions progress. Moreover, the lack of maintenance schedule causing data far from up to date as needed. Based upon the problem PT. SIER currently faced, kavling data management information system are necessarily required. This information system capable processing data management, data maintenance, data inquiry, maintenance schedule and occupation rate calculation. This kavling data management information system can produce kavling digital map by utilizing Googlemap API, kavling track record report, investor track record report, maintenance schedule report and kavling occupation rate report.Keyword: Information System, Management, Kavling